Tamponade Jantung sebagai Komplikasi Efusi Pleura pada Pasien Chronic Kidney Disease (CKD): Laporan Kasus - Izzati Adha Pratitis; Kurhayati Kurhayati; Kurnia Nasrullah; Ayu Prawesti Priambodo; Ristina Mirwanti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Chronic Kidney Disease (CKD) frequently presents multisystem complications, including pleural effusion and severe cardiovascular manifestations such as cardiac tamponade. Cardiac tamponade induced by massive pleural effusion is rare but life-threatening if not promptly managed.  A 17-year-old male patient presented to the emergency department with complaints of shortness of breath, bilateral lower extremity edema for four months, high-grade fever, and foamy urine. History revealed poorly controlled post-infectious glomerulonephritis complicated by heart failure. Physical examination demonstrated fluid overload, gallop rhythm, muffled heart sounds, subcostal retractions, and pulmonary edema. The patient's condition rapidly deteriorated, leading to cardiogenic shock due to cardiac tamponade and bilateral pleural effusions. Bilateral chest tube placement, furosemide therapy, and vasopressor support led to significant clinical improvement.  This case illustrates the complex interplay between chronic kidney disease, pleural effusion, and severe cardiac complications. Although pleural effusions in CKD patients are commonly transudative, massive bilateral effusions can cause extrinsic pressure sufficient to induce cardiac tamponade. Prompt and comprehensive management, patient education, and adherence to long-term treatment are crucial. This case highlights the importance of a multidisciplinary approach in managing multisystem complications of CKD, particularly acute situations such as cardiogenic shock resulting from cardiac tamponade induced by bilateral pleural effusion. Aggressive management, including pleural and pericardial drainage, supportive therapy, and adherence to regular follow-up, are essential for favorable long-term outcomes. Keywords: CKD, Pleural Effusion, Cardiac Tamponade, Cardiogenic Shock, Nephrotic Syndrome.  ABSTRAK Penyakit Ginjal Kronis (Chronic Kidney Disease/CKD) dapat menimbulkan komplikasi multisistem, termasuk efusi pleura dan gangguan kardiovaskular berat seperti tamponade jantung. Tamponade jantung akibat efusi pleura masif merupakan kasus yang jarang terjadi tetapi dapat mengancam jiwa apabila terlambat ditangani. Pasien remaja laki-laki berusia 17 tahun datang ke IGD dengan keluhan sesak napas, edema ekstremitas bawah selama empat bulan, demam tinggi, dan urin berbusa. Riwayat menunjukkan glomerulonefritis pasca infeksi disertai gagal jantung yang tidak terkontrol secara teratur. Pemeriksaan fisik menunjukkan tanda overload cairan, gallop, suara jantung teredam, retraksi subkostal, dan edema paru. Pasien mengalami perburukan kondisi dengan syok kardiogenik akibat tamponade jantung serta efusi pleura bilateral. Intervensi berupa pemasangan chest tube bilateral, pemberian furosemid, dan terapi vasopresor menghasilkan perbaikan signifikan.  Kasus ini menegaskan hubungan kompleks antara gangguan ginjal kronis, efusi pleura, dan komplikasi jantung yang serius. Efusi pleura pada CKD sebagian besar bersifat transudatif, namun kondisi ini dapat berkembang menjadi eksaserbasi akut berupa tamponade jantung akibat tekanan eksternal dari efusi pleura masif. Penanganan harus cepat, komprehensif, serta didukung edukasi keluarga dan kepatuhan pasien terhadap pengobatan jangka panjang. Kasus ini memperlihatkan pentingnya pendekatan multidisiplin dalam pengelolaan komplikasi multisistem CKD, terutama dalam situasi klinis akut seperti syok kardiogenik akibat tamponade jantung yang dipicu efusi pleura bilateral. Penatalaksanaan agresif yang mencakup drainase cairan pleura dan perikardial, terapi suportif, serta kepatuhan kontrol rutin adalah kunci utama keberhasilan terapi jangka panjang. Kata Kunci: CKD, Efusi Pleura, Tamponade Jantung, Syok Kardiogenik, Sindrom Nefrotik.